Characterization Study of Dyes Photodegradation-Adsorption Products by TiO2-Chitosan Immobilized on Glass Beads using Flow System - Mahadika, Bella Sukma; Saefumillah, Asep; Saepurahman, Saepurahman; Kurnia, Kiki Adi; Wellia, Diana Vanda (Syarif Hidayatullah State Islamic University, 2023)
Dyes have a complex molecular structure that is difficult to degrade and can persist for a long time in water bodies. This study examines more thoroughly the effectiveness of photodegradation-adsorption of dyes, kinetic aspects, isotherms, thermodynamics, identification of the structure of photodegradation products, and changes in environmental quality parameter values whose results are quite satisfactory. The combination of photodegradation-adsorption of dyes by TiO2-chitosan modified glass beads using a flow system has never been accomplished before. Flowing of the dye resulted in a dye degradation efficiency of 99%. The FESEM-EDX analysis shows that TiO2-chitosan has been coated onto the surface of the glass beads. R2 of kinetics MB, MO, RB are 0.99234, 0.9889, 0.9971, which were pseudo-first order. Qm, KL, R2 are 6.4382, 0.70533, 0.99923; 16.7364, 1.42059, 0.98816; 6.0078, 1.06973, 0.99889, respectively. The ∆H, ∆S, ∆S of -9.388, -0.024, -1.979; -27.182, -0.078, -3.592; -4.819, -0.017, 0.464 indicate the exothermic and spontaneous reaction. COD, TOC, pH, turbidity values have reached the threshold required by the government. The degradation products formed during the photodegradation-adsorption process were identified using LC-MS that the structure of the dye has been degraded to become simpler so that it is safely disposed of into the environment.